Limitações digitais comportamentais e de acesso entre participantes de rede social virtual: um estudo sobre gerenciamento de impressões no facebook - Medeiros, Sheyla Natália de (2013)
This work is part of the theme of digital limitation, broader than the concept commonly referred to in the literature as digital divide or digital exclusion. Three dimensions are found in digital limitation - access, informational and cognitive-behavioral - besides complex relationships. The research makes use of two of these dimensions, access limitation and behavioral limitation. Was chosen to study the management of impressions defined as all the activities that an individual develops with the aim to be always in evidence and influence the way they others see, in other words, the image or impression that the people create about this person. The focus of the research was to know the influence of impression management performed by a user on the effectiveness of another user in the use of a virtual social network they shared.For the achievement of the research, the social networking site Facebook was chosen, the research participants are individuals who consider themselves harmed and uncomfortable with the practice of impression management. The methodological procedures consisted of two focus groups and interview, in order to determine the effectiveness of use of virtual social networks, identify any damage to the effectiveness of the use of virtual social networks caused by impression management and explore the possible relationship between behavioral digital limitations of an individual and access digital limitations of another individual. The results allowed to realize that the effectiveness of the use of virtual social network is closely related to time optimization, the most harmful factors were identified as being the exaggerated frequency for sharing information, the theme of this information and also the high visibility imposed by some individuals. Was possible to verify that behavioral limitation of an individual affects how another person acts in their social network, by blocking information, deleting contacts, setting an access limitation.